Can someone here help me establish that $\lim\limits_{t \rightarrow \infty} S(t) = \Lambda/\mu$, given that:

$\frac{dS}{dt}=\Lambda-\mu S-\beta \frac{S}{N}(H+C+C_1+C_2)-\tau \frac{S}{N}(T+C)$


$\Lambda,\beta,\tau,\mu > 0$

$\text{As} \ \ t \rightarrow \infty, \ T,H,C,C_1,C_2 \rightarrow 0?$

My attempt:

$\frac{dS}{dt}=\Lambda-\mu S-\beta \frac{S}{N}(H+C+C_1+C_2)-\tau \frac{S}{N}(T+C) \leq \Lambda-\mu S.$ Clearly if $S > \Lambda/\mu,$ then $dS/dt<0.$ Since $dS/dt$ is bounded by $\Lambda-\mu S,$ a standard comparison theorem can be used to show that $S(t) \leq S(0)e^{-\mu t} + \frac{\Lambda}{\mu}(1-e^{-\mu t}).$ In particular, $S(0) \leq \frac{\Lambda}{\mu} \Rightarrow S(t) \leq \frac{\Lambda}{\mu}.$

Also, since $T,H,C,C_1,C_2 \rightarrow 0 \ \ \text{as} \ \ t \rightarrow \infty,$ $$(\forall \delta>0)(\exists T>0)\left(t \geq T \implies \left|-\beta\frac{S}{N}(H+C+C_1+C_2)-\tau\frac{S}{N}(T+C)\right|<\frac{\delta}{2}\right).$$ If we take $S \geq \frac{\Lambda-\delta}{\mu},$ then $\Lambda-\mu S \leq \delta.$

Hence $\frac{dS}{dt}=\Lambda-\mu S-\beta \frac{S}{N}(H+C+C_1+C_2)-\tau \frac{S}{N}(T+C) \leq \frac{3\delta}{2}.$

If we take $S \leq \frac{\Lambda+\delta}{\mu},$ then $\Lambda-\mu S \geq -\delta.$

Hence $\frac{dS}{dt}=\Lambda-\mu S-\beta \frac{S}{N}(H+C+C_1+C_2)-\tau \frac{S}{N}(T+C) \geq -\frac{3\delta}{2}.$

Question: How do I conclude?


One can synthetize the relevant assumptions as the fact that $S'(t)=\Lambda-\mu(t)S(t)$ where $\mu(t)\to\mu$ when $t\to\infty$ and $\mu\gt0$.

For every $\nu\gt\mu$, there exists some $t_\nu$ such that $\mu(t)\leqslant\nu$ for every $t\geqslant t_\nu$. Then $S'(t)\geqslant\Lambda-\nu S(t)$ for every $t\geqslant t_\nu$. The RHS is positive for every $S(t)\lt S_\nu$, where $$S_\nu=\Lambda/\nu,$$ hence, if $S(t)\lt S_\nu$ for some $t\geqslant t_\nu$, then the function $t\mapsto S(t)$ is increasing until $S(t)\geqslant S_\nu$ hence $\liminf\limits_{t\to\infty}S(t)\geqslant S_\nu$. Likewise, for every positive $\nu\lt\mu$, $\limsup\limits_{t\to\infty}S(t)\leqslant S_\nu$.

Thus, $S_{\mu+\varepsilon}\leqslant\liminf\limits_{t\to\infty}S(t)\leqslant\limsup\limits_{t\to\infty}S(t)\leqslant S_{\mu-\varepsilon}$ for every positive $\varepsilon\lt\mu$. When $\varepsilon\to0^+$, $S_{\mu+\varepsilon}\to S_\mu$ and $S_{\mu-\varepsilon}\to S_\mu$, hence $\liminf\limits_{t\to\infty}S(t)=\limsup\limits_{t\to\infty}S(t)=S_\mu$, that is, $\lim\limits_{t\to\infty}S(t)=S_\mu$.

  • $\begingroup$ Finish what? First, my answer is complete. Second, the proof in your comment is absurd. $\endgroup$ – Did Jan 4 '15 at 16:40
  • $\begingroup$ ((Comment by the OP deleted.)) $\endgroup$ – Did Jan 4 '15 at 17:18
  • $\begingroup$ Before "thus", one establishes a lower bound on the liminf and an upper bound on the limsup. After "thus", one puts them together. Thus, "thus". (And imbecility is off-topic here.) $\endgroup$ – Did Jan 4 '15 at 18:05
  • 1
    $\begingroup$ Sure, since the lower bound on the liminf holds for every $\nu\gt\mu$ and the upper bound on the limsup holds for every $\nu\lt\mu$. $\endgroup$ – Did Jan 4 '15 at 18:11

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.